DETECTION OF FLOOD IMPACTED AREAS IN EAST NUSA TENGGARA USING SENTINEL-1 IMAGERY - Bagas Aryaseta (CI-TECH, 2021)
Flash Floods in East Nusa Tenggara occured on April 4th, 2021. These Flash Floods are scattered from East Flores Regency, Lembata Regency, Alor Regency, Malacca Regency, Sabu Raijua Regency, Kupang City, Kupang Regency, and Ende Regency. The cause of these Flash Floods is the high intensity of rain caused by the tropical cyclone Seroja. Mapping of flood locations plays an important role in prevention and mitigation efforts. In this study, InSAR data processing was carried out from the Sentinel 1A satellite to find flood-affected locations in East Nusa Tenggara. 32 images of Sentinel-1 were processed before and 31 images after the Flash Floods incident. The method used is the classification method using cloud computing, Google Earth Engine. The results show that the flood-affected areas can be detected based on a lower pixel value (indicating a very small signal backscatter value), then compared to the conditions before the flood. The four sample points identified, namely points A, B, C, and D each have pixel values ​​of -8.58, -9.99, -12.43, and -9.29 for the VV polarized image, respectively. For VH polarized image is -17.35, -17.96, -17.84, and -14.22, respectively.